Pax ethnica : where and how diversity succeeds - Meyer, Karl E. (Karl Ernest), 1928-2019 (PublicAffairs, 2012)
Explores places noted for minimal violence, rising life-expectancy, high literacy, and pragmatic compromises on cultural rights, documenting the ways and means that have proven successful in defusing ethnic tensions and maintaining peace.